2009
DOI: 10.1002/jso.21226
|View full text |Cite
|
Sign up to set email alerts
|

Clinically important aspects of lymph node assessment in colon cancer

Abstract: There has been considerable discussion in the literature regarding the importance and validity of lymph node retrieval and lymph node count for patients with colon cancer. In this article we summarize the importance of lymph node resection and assessment in contemporary colon cancer care, key clinical determinants of lymph node assessment, and discuss the role of lymph node assessment as a quality marker in colon cancer care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
48
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 58 publications
1
48
0
Order By: Relevance
“…A probable proxy for thoroughness of colon cancer care (effective staging and treatment), lymph node evaluation depends on the expertise of both surgeons and pathologists. [47][48][49] Patients with surgically resected stage II or III colon cancer are the most likely to benefit from valid staging and adjuvant chemotherapies; in this group, lower income was associated with less thorough lymph node evaluation in San Francisco but not in Toronto. Among highincome patients, however, lymph node evaluation was more thorough in San Francisco than in Toronto.…”
Section: Depiction Of Two-and Three-way Interactionsmentioning
confidence: 99%
“…A probable proxy for thoroughness of colon cancer care (effective staging and treatment), lymph node evaluation depends on the expertise of both surgeons and pathologists. [47][48][49] Patients with surgically resected stage II or III colon cancer are the most likely to benefit from valid staging and adjuvant chemotherapies; in this group, lower income was associated with less thorough lymph node evaluation in San Francisco but not in Toronto. Among highincome patients, however, lymph node evaluation was more thorough in San Francisco than in Toronto.…”
Section: Depiction Of Two-and Three-way Interactionsmentioning
confidence: 99%
“…These studies have shown that higher lymph node yield is associated with better survival after colon cancer surgery [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The recommended number of nodes for appropriate staging is a minimum of 12 (5), although this goal has been achieved in as low as 50% of the patients (6). Factors associated with either a poor (<12 nodes) or adequate (≥12 nodes) LN harvest is the subject of extensive debate (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%